(untitled) (World Bulletin of Social Sciences, 2025)
The article explores methodological approaches to the formation and development of artistic thinking among future teachers. It analyzes the role of creative strategies, interactive teaching methods, and aesthetic education in the context of modernized education. Special attention is given to the effective use of information and communication technologies to enrich students’ thinking